East Asia: Chile S Missed Opportunity? - Dingemans-Calderon, A (Kluwer Academic Publishers, 2014)
East Asia is regarded in Chile as an opportunity to achieve economic development, because economic integration would place it in East Asia s value chains. This article suggests that the results of Chile s economic strategy toward East Asia, based on trade agreements, have had a predominantly quantitative success. The value of exports toward East Asia has indeed increased impressively. However, the qualitative results are less impressive. These agreements are not adequate to achieve structural change, which would enable the Chilean economy to move along East Asia s value chains. Statistical evidence confirms that Chile is still reduced to a commodity supplier and at the periphery of the chain. To change this situation, Chile has to design first a strategy of how to offer East Asia goods and services beyond commodities. This means looking beyond trade agreements. © 2014 Springer Science+Business Media Dordrecht.